Inclusive tourism: Assessing the accessibility of Lisbon as a tourist destination - Rebelo, S.; Patuleia, M.; Dias, Á. (Tourism and Hospitality, 2022)
Full accessibility to people with reduced mobility, applied to tourism, is difficult to achieve and should not be seen in an absolute way, but as a concern to make tourism services more accessible and focused on the specific and individual needs of people as tourists. National and regional entities should adopt good practices to build a tourism of all, for all. The Delphi method was used in order to verify the accessibility and attractiveness of the city of Lisbon as a tourist destination by addressing the following objectives: to analyse the competitiveness of a destination for people with reduced mobility, to analyse if Lisbon is attractive and inclusive, considering its infrastructures, services, hospitality, tourist attractions and accessibility. The results obtained in the study show that Lisbon’s factors and resources are increasingly accessible to people with reduced mobility. Our findings reveal that entertainment, general and tourism infrastructures, accommodation, the various activities and cultural resources and the quality of services present greater accessibility for people with reduced mobility. The factors with less importance were: marketing of a destination, accessibilities, and natural resources.